Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1021/cm00018a018
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of the europium(3+) ion in zirconium(4+) compounds

Abstract: The luminescence of the Eu3+ ion in some Zr4+ compounds is reported in order to study the influence of the effectively negative charge of the Eu3+ ion on the quantum efficiency for charge-transfer excitation.This effectively negative charge of the Eu3+ ion does not in principle enhance radiationless relaxation rates in the excited charge-transfer state, but the presence of vacancies in the structure may lower the efficiency considerably. For the Eu3+ luminescence in Zr02 and ZrPzO, the quantum efficiencies amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…Yet, this reduction has not been reported in the case of singly Eu 3+ doped ␣-Sr 2 P 2 O 7 . van der Voort [20] and Doat [21] reported that the solubility of Eu 3+ ions in pyrophosphate is limited and even at a small quantity of doped Eu 3+ a second EuPO 4 phase would be observed. The problem hinder the reduction from Eu 3+ to Eu 2+ in air is that Eu 3+ cannot easily enter into the ␣-Sr 2 P 2 O 7 host and substitute the Sr 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Yet, this reduction has not been reported in the case of singly Eu 3+ doped ␣-Sr 2 P 2 O 7 . van der Voort [20] and Doat [21] reported that the solubility of Eu 3+ ions in pyrophosphate is limited and even at a small quantity of doped Eu 3+ a second EuPO 4 phase would be observed. The problem hinder the reduction from Eu 3+ to Eu 2+ in air is that Eu 3+ cannot easily enter into the ␣-Sr 2 P 2 O 7 host and substitute the Sr 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…41,42 The CT bands, also of interconfigurational nature, involve for instance the promotion of the ligand electrons to the metal ion and usually occur in the UV region. 24,[41][42][43][44] For the case of Eu 3+ in oxide hosts, the promotion of an electron from a ground state configuration 4f 6 to the lowest 4f 5 5d level occurs in the UV and vacuum UV spectral region. [41][42][43][44] On the other hand, the CT transitions are known to occur at longer wavelengths than the f -d transitions and their peak positions are known to decrease in energy with larger average distance of the surrounding anions.…”
Section: Resultsmentioning
confidence: 99%
“…5͒ correspond to two different CT transitions as also detected in other zircon based compounds. 24 Considering the relative intensity of the absorption bands in the PLE spectra, the Eu 3+ luminescence from the 5 D 0 level is preferentially populated by CT mechanisms rather than the intra-4f 6 Eu 3+ excited levels. A comparison between the PL spectra obtained with excitation in the CT region and in the intra-4f 6 excited states ͑above the 5 D 2 level͒ can be observed in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zirconium(IV) pyrophosphate, ZrP 2 O 7 , represents a technologically important material, which has already found its application as high temperature proton conductor [1,2], catalyst [3], a host for luminescence materials [4][5][6], dielectric material [7], high density refractory [8,9] and ceramic with unique thermal expansion properties [10][11][12]. Despite the high attention to the ZrP 2 O 7 phase, there are only a few reports on heterovalent substitutions in its structure.…”
Section: Introductionmentioning
confidence: 99%